2019
DOI: 10.1111/jam.14210
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of sea buckthorn (Hippophae rhamnoides) pulp oil‐based mouthwash on oral health

Abstract: Aim The purpose of this study was to conduct phytochemical analysis of sea buckthorn pulp oil and to evaluate the antimicrobial, anti‐biofilm and antioxidant activities of its mouthwash form. Methods and Results Fatty acid composition of the sea buckthorn pulp oil was determined by GC‐MS analysis, which revealed that, mono‐unsaturated fatty acid, palmitoleic acid and saturated fatty acid, palmitic acid, were the major constituents. The antimicrobial and the anti‐biofilm capacities of sea buckthorn pulp oil mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
(66 reference statements)
0
15
1
Order By: Relevance
“…The present work indicated that the physicochemical values of the oil are not well within value reported in the literature but it is due to the state of i.e. crude and change of the climate from the others, but the oil does not seem the change its property and utilization as oil and medicine in recommended diseases [25].…”
Section: Figure 2 Gas Liquid Chromatographycontrasting
confidence: 74%
See 1 more Smart Citation
“…The present work indicated that the physicochemical values of the oil are not well within value reported in the literature but it is due to the state of i.e. crude and change of the climate from the others, but the oil does not seem the change its property and utilization as oil and medicine in recommended diseases [25].…”
Section: Figure 2 Gas Liquid Chromatographycontrasting
confidence: 74%
“…The chart speed was adjusted to 10 mm/min. The peaks recorded at shimadzu recorder C-R4A chromatopac, were identified by comparison of their retention times with those of standard methyl esters analyzed under the same conditions [25]. The area of each peak was calculated by the formula; Area of peak = 1/2 x base perpendicular.…”
Section: Gas Liquid Chromatographymentioning
confidence: 99%
“…Cosmetic products made of Hippophae plants include shampoo, skin cream and bath soak [102]. Smida [105] evaluated the antioxidant activities of sea buckthorn-based mouthwash; the free radical-scavenging activity of sea buckthorn was assessed by DPPH and superoxide anion scavenging (NBT) assays to elucidate the role of sea buckthorn in reducing oxidative stress and damage linked to periodontitis. The results suggested that the superoxide radical-scavenging activities of the sea buckthorn pulp oil-based mouthwash increased markedly with increasing concentrations, suggesting that the mouthwash is a potent scavenger of superoxide radicals.…”
Section: Cosmetic Values Of Hippophae Speciesmentioning
confidence: 99%
“…Also, Hou et al 2017proved that treatment with SB oil could suppress the development of atopic dermatitis-like lesions in mice, possibly proving the regenerating capacity of SB fruit oil. Smida et al (2019) have interestingly proved the efficacy of SB pulp oil as a mouthwash product. They found that a preparation containing SB pulp oil could have a bactericidal and anti-biofilm activities against oral bacteria species, although antifungal activities were not proved.…”
Section: Health Benefits Of Sea Buckthorn: Recent Advancesmentioning
confidence: 96%